Factors influencing Generation Z students' participation in the Indonesian International Student Mobility Awards program in Bali - Sadguna, I Gde Agus Jaya; Sari, I Gusti Agung Mas Krisna Komala (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims at establishing the factors that affect the participation of the Generation Z students for the Indonesian International Student Mobility Awards (IISMA) program in Bali. Using a mixed-method approach, the research identifies key academic, personal, and environmental factors influencing student decisions. The study utilizes semi-structured interviews and questionnaires to 29 recipients of IISMA scholarship from four higher education institutions based in Bali, and qualitative research method was used in the form of thematic analysis for the data. Concerning personal factors, it was clear that competitive global exposure and career advancement as well as personal growth were of high importance. Under For academic factors, opportunities for research, added coursework, and the allure of some of the most competitive universities in the world were found. Under environmental factors, the need for cultural engagement, possibilities of networking and full funding were mentioned. The context of the post-pandemic period, in which participation selections took place appeared to carry a great weight. Results show that members of Generation Z view international education methods comprehensively, reconciling one's pursuit of personal objectives with one's pragmatic concerns about having a rewarding profession. It is therefore argued that the IISMA scheme in Bali is of great appeal to Gen Z because it offers at the same time academic standing and opportunities for cultural experience. These results contribute towards understanding the variable trends in student mobility and can also assist in designing international education programs that aim at the needs and ambitions of Generation Z.